Efektifitas Larutan Iodin Sebagai Indikator Pada Pengukuran Pengaruh Pemanasan Terhadap Kandungan Vitamin C Minuman Sari Buah - Raekhan Rahmah Putri; Ahmad Gunawan Wibisono; Mohammad Rayhan Afdillah; Feni Aryanti; Mardiyana Mardiyana; Murni Handayani (Politeknik Negeri Cilacap, 2021)
Vitamin C is one of the micronutrients needed in the body. The need for vitamin C can be met by consuming fruits and vegetables. Vitamins are easily damaged due to heating time. There are several methods developed to determine the content of vitamin C in food and one of them is the iodometry method. The iodometric method is considered simpler and easier to do in testing the content of vitamin C in food and beverages. The purpose of this study was to determine the effectiveness of iodine indicators in measuring the content of vitamin C in several types of packaged fruit juice drinks and original fruit juices that had been treated with different heating. From the results of testing and literature studies regarding the effect of heating time on vitamin C content in fruit juices, it shows the suitability of a decrease in vitamin C content. This shows that a simple iodometric method is quite effective in showing the results of measuring vitamin C content in samples.